2020
DOI: 10.7759/cureus.7984
|View full text |Cite
|
Sign up to set email alerts
|

The Need for More Mentorship in Medical School

Abstract: IntroductionMentorship, a supportive relationship that actively provides knowledge and insight, has many benefits. Although not extensively studied, medical students pursuing various specialties have diverse experiences with mentorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…This is significant because, these data suggest both that students are successfully able to establish relationships with neurosurgical faculty who are open to becoming mentors, and that students often must take the initial step to establish said relationships. Recent research suggests that medical students are unsatisfied with the amount of mentorship they receive in medical school by-in-large,[ 3 ] and numerous reports have suggested that acquiring mentors and differential access to mentors can contribute to barriers in pursuing certain medical specialties, especially for students underrepresented in medicine. [ 12 , 15 , 19 ] Notably, over half of the students in our sample reported completing their research projects as a part of a facilitated fellowship program.…”
Section: Discussionmentioning
confidence: 99%
“…This is significant because, these data suggest both that students are successfully able to establish relationships with neurosurgical faculty who are open to becoming mentors, and that students often must take the initial step to establish said relationships. Recent research suggests that medical students are unsatisfied with the amount of mentorship they receive in medical school by-in-large,[ 3 ] and numerous reports have suggested that acquiring mentors and differential access to mentors can contribute to barriers in pursuing certain medical specialties, especially for students underrepresented in medicine. [ 12 , 15 , 19 ] Notably, over half of the students in our sample reported completing their research projects as a part of a facilitated fellowship program.…”
Section: Discussionmentioning
confidence: 99%
“…An initial questionnaire was created by members of the REMED-UK steering committee based on literature ndings [10,12,[21][22][23][24][25][26][13][14][15][16][17][18][19][20]. The initial questionnaire was sent to the REMED-UK regional leads (students across various UK medical schools) for feedback.…”
Section: Questionnairementioning
confidence: 99%
“…A atividade de mentoria pode ser vista como um relacionamento especial que se desenvolve como uma via de mão dupla, mas no início do curso de Medicina pode ser de mão única, com o mentor dirigindo a conversa e as atividades 1,2 . À medida que o relacionamento amadurece, a orientação aos estudantes pode estar associada a uma maior reflexão do mentor, impactando sua maneira de conduzir as discussões e ponderações 1,3 .…”
Section: Introductionunclassified
“…A atividade de mentoria pode ser vista como um relacionamento especial que se desenvolve como uma via de mão dupla, mas no início do curso de Medicina pode ser de mão única, com o mentor dirigindo a conversa e as atividades 1,2 . À medida que o relacionamento amadurece, a orientação aos estudantes pode estar associada a uma maior reflexão do mentor, impactando sua maneira de conduzir as discussões e ponderações 1,3 . O contato frequente associado à energia e ao entusiasmo dos estudantes pode provocar novas formas de desenvolvimento individual e proporcionar, aos estudantes e ao mentor, maior satisfação acadêmica com consolidação gradativa da parceria na busca do aprender a aprender 3 .…”
Section: Introductionunclassified